Perancangan Perbaikan Kualitas Biji Kopi Di UMKM Lestari Kopi - Saputra, Aditya; Chandrahadinata, Doddy (Jurnal Kalibrasi, 2024)
The research aims to identify product defect problems, determine product defect factors and design improvements in product defects in UMKM Lestari Kopi. Based on information from the owner of Lestari Kopi, there are defects in the coffee beans caused by the machine, for example, the coffee beans are broken, then the coffee beans are moldy caused by a lack of operators turning the coffee beans back and forth when drying and flattening caused by the time when the coffee beans are not yet in the upstream, but they are forced to be upstream due to sudden consumer needs. The data processing method uses Six Sigma with the DMAIC stage, in the Define stage it collects production data and defect data from the previous period and makes a CTQ, in the Measure stage it performs calculations to make a pareto diagram, DPMO whose results are converted to the sigma table and a C chart is made. At the analysis stage, it was carried out using the FMEA method, where the results of the highest RPN were prioritized for improvement. The Improve stage uses the Five W One H concept (5W + 1H) to regulate the corrective actions to be carried out resulting in a replacement of the grinding wheel. And the control stage implements the results of the corrective actions resulting from the defect rate of the coffee product decreasing with a defect percentage of 6%. which was previously at 14%, therefore an SOP was created to ensure that each job carries out activities correctly, quickly and avoids errors.